Thrombotic risk correlates with mutational status in true essential thrombocythemia. (6th July 2016) - Bertozzi, Irene; Peroni, Edoardo; Coltro, Giacomo; Bogoni, Giulia; Cosi, Elisabetta; Santarossa, Claudia; Fabris, Fabrizio; Randi, Maria L.
Abstract: Background: True essential thrombocythemia (ET) may carry one of the known driver mutations ( JAK2, MPL and CALR ) or none of them [in triple‐negative (3NEG) cases]. The patients' mutational status seems to delineate the clinical manifestations of ET. Materials and methods: We report the data of 183 patients diagnosed with ET strictly according to the WHO 2008 criteria and with a full molecular diagnosis, including the following: 114 patients (62·3%) with JAK2 V617F; 25 (13·7%) with CALR type 1 and 19 (10·4%) with CALR type 2; 3 (1·6%) with MPL ; 22 (12%) who were 3NEG. Thrombotic risk was assessed by means of the IPSET‐thrombosis score (IPSET‐T). Results: CALR and 3NEG patients had lower haemoglobin levels and leucocyte count than JAK2 patients. CALR patients, and those with type 2 in particular, had higher mean platelet counts and had extreme thrombocytosis more often than any of the other groups. Based on their IPSET‐T stratification, 3NEG‐ and CALR ‐mutated patients belonged more frequently to the low‐risk group and had a significant more favourable thrombosis‐free survival rate than those with JAK2 mutation. Conclusion: These findings indicate that the three different molecular markers have a significant impact on the clinical course of true ET, giving rise to different phenotypes of the same disease.